2006
DOI: 10.1002/hep.21306
|View full text |Cite
|
Sign up to set email alerts
|

Gender and liver: Is the liver stiffness weaker in weaker sex?

Abstract: dition, several statements purely reflect the authors' opinion without giving reference to published literature data.We agree that the mechanisms by which ␤-catenin signaling might influence GS expression are not fully understood. However, in contrast to the statement that GS expression "is somehow dependent on ␤-catenin signaling", a fundamental role of ␤-catenin in regulation of GS expression has been clearly established by several groups: (i) GS is expressed in all hepatocytes of mice carrying an activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 9 publications
11
46
1
1
Order By: Relevance
“…This finding, which is consistent with the results of a previous study conducted on a small population of supposedly ''healthy subjects'' [12], indicates that gender should be taken into account when interpreting liver stiffness values. It also suggests the existence of intrinsic differences between men and women in the density of liver extracellular matrix [13], a hypothesis supported by previous studies showing that ovarian hormones inhibit extracellular matrix production by liver stellate cells [14].…”
Section: Discussionsupporting
confidence: 94%
“…This finding, which is consistent with the results of a previous study conducted on a small population of supposedly ''healthy subjects'' [12], indicates that gender should be taken into account when interpreting liver stiffness values. It also suggests the existence of intrinsic differences between men and women in the density of liver extracellular matrix [13], a hypothesis supported by previous studies showing that ovarian hormones inhibit extracellular matrix production by liver stellate cells [14].…”
Section: Discussionsupporting
confidence: 94%
“…The mean liver stiffness value in these patients was 5.5 ± 1.6 kPa. Age had no influence but as suggested previously [27], liver stiffness values were higher in men than in women (5.8 + 1.5 vs. 5.2 + 1.6 kPa, respectively; p = 0.0002), and in subjects with BMI > 30 kg/m2 (6.3 + 1.9 vs. 5.4 + 1.5 kPa, respectively; p = 0.0003). However, even after adjustment for gender and BMI, liver stiffness values remained higher in subjects with metabolic syndrome (n = 59; 13.7%) than in those without (6.5 + 1.6 vs. 5.3 + 1.5 kPa, respectively; p < 0.0001) (Fig.…”
Section: Normal Valuessupporting
confidence: 61%
“…According to transaminase levels, 19 of 95 patients with CD (20%) showed an increase in ALT and/or AST values that could suggest a liver impairment, whereas an actual hepatic involvement, evaluated by TE, was detected in only 10 CD patients. According to our data, significant or severe liver fibrosis is not a common finding in CD, thus confirming previous studies [54,59,60]. Moreover, from this study, the absolute values of TE observed in patients with CD were within the reference range, considering the group of healthy subjects as controls.…”
Section: Discussionsupporting
confidence: 93%